2017
DOI: 10.3390/s17081771
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Coverage for 3D Camera Sensor Networks

Abstract: Barrier coverage, an important research area with respect to camera sensor networks, consists of a number of camera sensors to detect intruders that pass through the barrier area. Existing works on barrier coverage such as local face-view barrier coverage and full-view barrier coverage typically assume that each intruder is considered as a point. However, the crucial feature (e.g., size) of the intruder should be taken into account in the real-world applications. In this paper, we propose a realistic resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Thus, the work in [ 16 , 17 , 18 ] assumed the probabilistic sensing model. Moreover, state-of-the-art research work considers more practical issues such as the utilization of the three-dimensional (3D) sensing model in camera sensor networks [ 19 ] and the joint probability model in the compound event barrier coverage problem [ 20 ]. However, we adopt the Boolean disc sensing model in our research since we are the first to study the crossed barrier coverage problem.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the work in [ 16 , 17 , 18 ] assumed the probabilistic sensing model. Moreover, state-of-the-art research work considers more practical issues such as the utilization of the three-dimensional (3D) sensing model in camera sensor networks [ 19 ] and the joint probability model in the compound event barrier coverage problem [ 20 ]. However, we adopt the Boolean disc sensing model in our research since we are the first to study the crossed barrier coverage problem.…”
Section: Related Workmentioning
confidence: 99%
“…Wutthigrai Boonsuk [16] implemented a stereo vision system for industrial robotics and concluded the following: shorter baseline distances performs better at shorter distances to the target, but at longer distances, wide baselines are better. Si et al [17] used camera sensor networks to detect intrusions passing through a barrier area. They implemented multiple parallel cameras in order to guarantee a maximum coverage for the monitored barrier.…”
Section: Disparity Maps In Wireless Multimedia Sensor Networkmentioning
confidence: 99%
“…With the development of embedded systems and communication technology, wireless multimedia sensor networks (WMSN) have assumed a prominent scientific position [1,2]. Accordingly, WMSN constitute a winning solution with their information acquisition method and processing technology, and allow the acquisition of complete information in the monitoring area, especially video data [3]. They have been extensively used in different applications, such as military affairs, public security, environmental monitoring/forecasting, home automation, and in intelligent transportation [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the importance of WMSN, researchers have conducted extensive studies in this area [7,8]. Most of the existing studies have concentrated on localization [9], barrier coverage [3], data fusion [10], and sensor deployment [11]. Among these studies, the sensor network deployment problem guarantees the coverage of the monitoring area corresponding to the sensors, and provides the foundation of all the upper-layer applications.…”
Section: Introductionmentioning
confidence: 99%